The Analysis of Reading Habits Using Miles and Huberman Interactive Model to Empower Students’ Literacy at IPB Cirebon - Lili Sururi Asipi; Utami Rosalina; Dwi Nopiyadi (Ilmu Inovasi Nusantara, 2022)
The purpose of this study is to describe the reading habits of students of the English Education Study Program of IPB Cirebon and to find out several factors that influence the habits of students of IPB Cirebon. This study uses a qualitative method using an ethnographic approach. The Source of data is taken by purposive sampling or sample purpose. Data were collected using in-depth interviews, active participant observation, and questionnaires. Data accuracy was validated by data triangulation, method triangulation, and member check. Furthermore, the data were analyzed using the Miles and Huberman interactive model. The results of this study describe reading habits in six indicators, reading frequency, type of reading, number of readings, visiting the library, the purpose of reading, and awareness of the importance of reading. Indicators of reading frequency, type, and amount of reading still need to be developed because students still depend on assignments or academic activities given by lecturers. Indicators of student reading habits that need further development are related to the discipline of using time and ownership of periodic readings in newspapers, magazines, scientific magazines, or journals. The need for information is obtained from social media but not regularly and periodically. Access to information is done depending on the mood or mood. Therefore, there are three important points: family, education, and internet use. Indicators of student reading habits that need further development are the discipline of using time and ownership of periodic readings in newspapers, magazines, scientific magazines, or journals. The need for information is obtained from social media but not regularly and periodically. Access to information is done depending on the mood or mood. Therefore, there are three important points: family, education, and internet use. Indicators of student reading habits that need further development are the discipline of using time and ownership of periodic readings in newspapers, magazines, scientific magazines, or journals. The need for information is obtained from social media but not regularly and periodically. Access to information is done depending on the mood or mood. Therefore, there are three important points, namely family, education, and internet use